2013
DOI: 10.1038/onc.2013.456
|View full text |Cite
|
Sign up to set email alerts
|

p73 regulates serine biosynthesis in cancer

Abstract: Activation of serine biosynthesis supports growth and proliferation of cancer cells. Human cancers often exhibit overexpression of phosphoglycerate dehydrogenase (PHGDH), the metabolic enzyme that catalyses the reaction that diverts serine biosynthesis from the glycolytic pathway. By refueling serine biosynthetic pathways, cancer cells sustain their metabolic requirements, promoting macromolecule synthesis, anaplerotic flux and ATP. Serine biosynthesis intersects glutaminolysis and together with this pathway p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 47 publications
1
105
0
Order By: Relevance
“…Metabolic regulation by p53 family appears a key function for their cancer-related but also ageing-related phenotype. All the three members promote mitochondrial respiration thought regulation of different metabolic enzymes, including the glutaminase 2 (Gls2) (Adamovich et al, 2014;Amelio et al, 2014b;Bellomaria et al, 2010Bellomaria et al, , 2012Giacobbe et al, 2013;He et al, 2013;Hu et al, 2010;Sharif et al, 2015;Simon et al, 2014;Velletri et al, 2013;Viticchie et al, 2015). Gls2 regulates glutamine utilization, supplying anaplerotic flux of substrates resulting in promotion of mitochondrial activity and ATP synthesis (Amelio et al, 2014a;Maniam et al, 2015).…”
Section: Oxygen Tension Hypoxia Inducible Factors and Ageing Relatedmentioning
confidence: 99%
“…Metabolic regulation by p53 family appears a key function for their cancer-related but also ageing-related phenotype. All the three members promote mitochondrial respiration thought regulation of different metabolic enzymes, including the glutaminase 2 (Gls2) (Adamovich et al, 2014;Amelio et al, 2014b;Bellomaria et al, 2010Bellomaria et al, , 2012Giacobbe et al, 2013;He et al, 2013;Hu et al, 2010;Sharif et al, 2015;Simon et al, 2014;Velletri et al, 2013;Viticchie et al, 2015). Gls2 regulates glutamine utilization, supplying anaplerotic flux of substrates resulting in promotion of mitochondrial activity and ATP synthesis (Amelio et al, 2014a;Maniam et al, 2015).…”
Section: Oxygen Tension Hypoxia Inducible Factors and Ageing Relatedmentioning
confidence: 99%
“…The GSH-dependent antioxidant response of cancer cells may benefit depending on the availability of serine, which can be transformed into glycine through the serine hydroxymethyltransferase (SHMT). [104][105][106] Interestingly, it has been demonstrated that cancer cells lacking p53 are protected from oxidative stress-induced by serine depletion in the presence of p73, a p53 family member that has the ability to drive serine biosynthesis de novo 107,108 and to increase the pentose phosphate shunt and nucleotide biosynthesis via G6PD. 109,110 Thus, the p73 overexpression detected in various primary RMS samples 111 may have an important role for oxidative stress resistance.…”
Section: Oxidative Stress Pathwaysmentioning
confidence: 99%
“…It was reported recently that, upon serine starvation, p53 activates p21 to promote GSH production to combat ROS [25,26]. Additionally, p73, ATF4, G9A, HIF1 and PKCζ were also reported to regulate serine biosynthesis and metabolism [27][28][29][30][31]. However, compared to the profound understanding of glycolysis and glutaminolysis in cancer cells, we are only beginning to appreciate the critical impact of serine synthesis pathway (SSP) on cancer progression.…”
Section: Introductionmentioning
confidence: 99%